2013
DOI: 10.1007/s00064-012-0215-2
|View full text |Cite
|
Sign up to set email alerts
|

Stadiengerechte Therapie des Kniegelenkinfekts nach Arthroskopie

Abstract: Arthroscopic irrigation with stage-related debridment of all 6 recesses in combination with antibiotic therapy is the standard procedure for knee joint infections when there is no arthroplasty. Open surgery with debridement of infected bone tissue is indicated in patients with stage IV according to Gächter. Decisive for good results is an early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…15,30 Regarding the arthroscopic technique, we did not use additional portals (eg, posteromedial/posterolateral) as suggested by other authors. 9,24 In exceptional cases, these might additionally be used but are not necessary in standard treatment. Further, we did not perform extended synovectomy to minimize surgical trauma and the risk for arthrofibrosis and to keep the synovial layer as a natural barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,30 Regarding the arthroscopic technique, we did not use additional portals (eg, posteromedial/posterolateral) as suggested by other authors. 9,24 In exceptional cases, these might additionally be used but are not necessary in standard treatment. Further, we did not perform extended synovectomy to minimize surgical trauma and the risk for arthrofibrosis and to keep the synovial layer as a natural barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Stage-adapted treatment regimens have been published, but they are not evidence based, and included case numbers are low. 9,12,24 Antibiotic therapy is controversially discussed, and evidence-based data are not available. Most authors recommend a minimum length of 4 weeks for antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If a high‐grade joint infection is already confirmed at the time of diagnosis (Gächter stage 4) by osteolysis using conventional radiography, an open procedure should be considered (Fig. 3) [27].…”
Section: Classification Of Septic Arthritismentioning
confidence: 99%
“…An arthroscopic versus an open approach can be debated, but multiple studies have demonstrated the safety and efficacy of arthroscopic treatment alone 2,42–46. If a high-grade joint infection (Gächter stage IV) is present and confirmed, an open approach should be utilized 47–49. Extensive irrigation and lavage with saline, thorough synovectomy with removal of infected or necrotic tissue, and possible hardware removal should be performed.…”
Section: Infection Risk Factors and Preventative Strategiesmentioning
confidence: 99%
“…2,[42][43][44][45][46] If a high-grade joint infection (Gächter stage IV) is present and confirmed, an open approach should be utilized. [47][48][49] Extensive irrigation and lavage with saline, thorough synovectomy with removal of infected or necrotic tissue, and possible hardware removal should be performed. Authors have suggested a minimum of 6 L of saline, however, no irrigation fluid volume is currently supported by the literature definitively.…”
Section: Irrigation and Debridementmentioning
confidence: 99%